Penanaman Sikap Kedisiplinan pada Santri Al-Masyhad Manbaul Falah Wali Sampang Pekalongan - Nurhazilna, Nurhazilna; Aini, Rofiqotul (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
Discipline problems are fundamental problems that need serious attention in shaping one's personality. Discipline is the pillars of character that must be instilled in each student. The habit of being disciplined at school or at Islamic boarding schools will have a positive influence on the life of students in the future. In accordance with what has been programmed by the pesantren. Of course, this activity has a goal to be achieved. This study uses a qualitative approach with a case study type of research and is descriptive in nature which aims to instill discipline in students. This research was conducted at the Al-Masyhad Manbaul Falah Islamic boarding school, Wali Sampang, Pekalongan. Data collection techniques use observation and interviews. The results of this study found that the strategy for cultivating the character of discipline for students at Pondok Al Masyhad Mambaul Falah Wali Sampang Pekalongan was divided into three, namely: 1) language discipline, 2) study discipline and 3) worship discipline. The three strategies in cultivating the character of discipline have been carried out to the fullest, so that this research is expected to become a reference/role model in the application of student discipline, especially at Islamic boarding schools.